Motives of Customer Deposits Window-Dressing in Indonesian Commercial Banks - Geraldina, Ira; Rossieta, Hilda; Utama, Sidharta (Asian Journal of Business and Accounting, 2015)
This study examines the motives of Indonesian commercial banks to window-dress their customer deposits at the end of the financial year. Prior studies indicate that one of the motives is to maintain liquidity since an increase amount of customer deposits can result in a decrease to the loan to deposit ratio as well as improve year-end cash balance, indicated by the liquidity reserve requirement ratio. Using the panel data analysis method, this study employed 272 observations of conventional commercial banks in Indonesia from 2009-2011. The empirical results show that liquidity reserve requirement ratio as proxy for short-term banks’ liquidity has negative effects on the level of banks’ window-dressing. However, the results do not support the long-term liquidity motive. In addition, the results indicate that the tendency for banks to practise customer deposits window-dressing is higher among smaller banks than large banks. The results suggest that a bank’s short-term bank liquidity ratio may not necessarily reflect the bank’s true liquidity condition. Keywords: Customer Deposits, Financial Reporting, Indonesian Banks, Liquidity, Real Earnings Management, Window-Dressing JEL Classification: M410